2018
DOI: 10.1038/s41467-018-07712-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong nanocrystalline steel with exceptional thermal stability and radiation tolerance

Abstract: Nanocrystalline (NC) metals are stronger and more radiation-tolerant than their coarse-grained (CG) counterparts, but they often suffer from poor thermal stability as nanograins coarsen significantly when heated to 0.3 to 0.5 of their melting temperature (Tm). Here, we report an NC austenitic stainless steel (NC-SS) containing 1 at% lanthanum with an average grain size of 45 nm and an ultrahigh yield strength of ~2.5 GPa that exhibits exceptional thermal stability up to 1000 °C (0.75 Tm). In-situ irradiation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…Various nanocrystalline materials have been developed for radiation resistance [29][30][31]. In coarse-grain material, the diffusion barrier of vacancies is high, and hence the irradiation-induced vacancies migrate slowly and hard to recombine with interstitial atoms.…”
Section: 2 Nanocrystalline Tungsten For Radiation Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Various nanocrystalline materials have been developed for radiation resistance [29][30][31]. In coarse-grain material, the diffusion barrier of vacancies is high, and hence the irradiation-induced vacancies migrate slowly and hard to recombine with interstitial atoms.…”
Section: 2 Nanocrystalline Tungsten For Radiation Resistancementioning
confidence: 99%
“…Recently, several ultra-uniform nanocrystalline materials were reported via a two-step sintering, which is expected to be used in the tungsten-based nanocrystalline [61,62]. Furthermore, doping elements precipitating around the boundary in the form of oxide nano-clusters could effectively stabilize nano-grain in austenite steel, and this strategy may also encourage the construction of stable tungsten-based nanocrystalline at elevated temperature [31].…”
Section: Challenges Of Nanocrystalline Tungstenmentioning
confidence: 99%
“…As a rapid characterization technique to assess thermal stability of NC and UF grained materials, performing in-situ transmission electron microscopy (TEM)/heating experiments has evolved, where thin specimen (preferably below 100 nm) are heated inside the TEM microscope while observing the changes in morphology. These experiments were used on different materials and the thermal stability of these materials in the pristine conditions and irradiated conditions (for nuclear materials) are concluded in some cases based on the in-situ TEM/heating observations [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…One major challenge is that the microstructure of metallic materials subjected to high-energy particle irradiation undergoes serious degradation, forming various types of defects, such as Frenkel pairs, dislocation loops, etc., which further undermine the mechanical properties of irradiated materials [12][13][14]. An effective way to mitigate irradiation-induced degradation in materials is to introduce high-density defect sinks [15], such as free surfaces [16], high angle grain boundaries [17,18], twin boundaries [19], and phase interfaces [20]. Recent ex situ proton and helium ion irradiation studies on AM 316 SS found that dense dislocations trapped inside solidification cellular structures tended to undergo recovery and recrystallization during radiation, and may serve as defect sinks, thus help alleviate void swelling and helium bubble formation [9,10].…”
Section: Introductionmentioning
confidence: 99%